PENERAPAN APLIKASI E-COMMERCE BERBASIS BUSINESS TO CONSUMERS PADA TOKO CANADA MENGGUNAKAN FRAMEWORK CODEIGNITER - David; Meyrisia Bella Melinda (PROGRESS, 2022)
Toko Canada is a company that sells various kinds of fashion needs for men and women. The system used in sales activities is still manual, which is still using notebooks in processing the data. So in carrying out sales activities is still difficult and takes a lot of time. There needs to be a sales system to facilitate sales activities. Business To Consumers is one of the e-commerce models, which is a business process where sales deal directly with buyers. Buying and selling directly through word of mouth is still done in the era of technological developments like now. However, the buying and selling process was deemed less efficient and the scope of sales was felt to be less extensive. So that these problems are not sustainable, an e-commerce business model website will be built for customers. In building an e-commerce system, the author uses the prototype method by designing the system using the Unified Modeling Language (UML). Then MySQL supported to manage existing databases. The final result of this research is an e-commerce system at Toko Canada that can help and facilitate various sales activities. The conclusion of this research is that the sales application that has been made makes it easy for owners to get accurate reports and can also help employees to record reports.